"Sefer Razi'el ha-Mal'akh" - A Conduit of Medieval Ashkenazi Culture - Idel, Mosheh (Aschkenas, 2024)
This essay examines Sefer Razi'el ha-Mal'akh, a complex work reflecting diverse textual sources and literary layers, as a crucial channel for transmitting early esoteric traditions in Ashkenazi religious culture. It emphasizes the "nominal register" related to the exegesis and uses of divine names as a key part of the Ashkenazi esoteric tradition. The popularity of Sefer Razi'el ha-Mal'akh in Ashkenaz, especially during the Hasidic renaissance, highlights the essential role of practical and magical mentality developed in Ashkenazi culture and traditions. Additionally, a Romanian translation of Sefer Razi'el ha-Mal'akh by Menachem Mendel Stein, who engaged in occult practices during the World War II, showcases the book's varied reception and long durée.